MEKANISME LAYANAN PEER TO PEER LENDING DALAM TINJAUAN SYARIAH BERDASARKAN FATWA DSN MUI No. 117/DSN-MUI/II/2018 (STUDI KASUS PT AMMANA FINTEK SYARIAH) - Durotin Masruroh; Nur Diana; Harun Alrasyid (El-Aswaq, 2021)
This study aims to explain the mechanism of Peer to Peer Lending services at PT Ammana Fintek Syariah and explain the application of DSN MUI Fatwa Number 117/DSN-MUI/II/2018 regarding Peer to Peer Lending products. The analysis uses qualitative methods with content analysis. The results of this study indicate that the Peer to Peer Lending service mechanism at PT Ammana Fintek Syariah has been registered and licensed at the OJK, there are three service mechanism products, namely Ammana funding, Hajj financing, and Ammana Paylater. Legally, it is in accordance with the DSN-MUI fatwa. The financing agreement sourced from PT. Ammana Fintek Syariah based on QS. Al-Anfaal verse 27 and Ijab Qobul in accordance with the QS. Al-Maidah paragraph 1. Application of Peer to Peer Lending products that are not in accordance with the DSN-MUI fatwa no. 117/DSN-MUI/II/2018 in the general provisions of point 19, namely Gharar. At PT. Ammana Fintek Syariah which is a product of Dana Ammana regarding contracts, there is confusion with the contracts used that are not in accordance with sharia principles